Environmental Risk Assessment of Metal Contamination of Agricultural Soils along Major Roads of Two Peri – Urban Areas in Nasarawa State, North Central, Nigeria - Jude Chinedu Onwuka; Jonathan Maduka Nwaedozie; Emmanuel Hala Kwon–Dung; Paul Tersoo Terna; Gladys Nkeiruka Nwobodo (Pandawa Institute, 2023)
This research focused on the level, pollution, and ecological risk assessment of selected heavy metals from agricultural soils at major roadsides in Nasarawa Eggon and Doma areas. Composite soil samples were collected at 0–20 cm depth, homogenised, and assayed for metal (As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, U and Zn) levels using the X–ray fluorescence technique. Pollution and toxicity of the studied metals were determined by evaluating enrichment factor (Ef), geo–accumulation index (Igeo), contamination factor (Cf), degree of contamination (Cd), pollution load index (PLI), and ecological risk assessment (ERA). The result showed that concentrations of As, Cd, Cr, Cu, Fe and Ni were lower than the average shale values, except for As of site N2 in the Nasarawa Eggon area and Fe of site D4 in the Doma area. The Ef suggests a significant anthropogenic contribution to the presence of As, Co, Hg, Mn, Pb and Zn in some of the sampled sites. The Igeo indicated that Nasarawa Eggon sampled soils were polluted by Hg and Pb while Hg and Co polluted those of Doma. The Cf values revealed that most of the soils were contaminated with Hg in addition to As, Co, Fe, Mn, and Zn in some sites. All sites have low Cd except N2 and N4 (Nasarawa Eggon) and D2 and D4 (Doma). However, PLI showed that only sites N2 and D4 were polluted. ERA revealed that As, Co, and Hg posed potential ecological risks ranging from low to a significant level in different sites. Sites N2, D2 and D4 showed a moderate ecological risk index. Therefore, this study showed significant anthropogenic inputs from automobile emissions and human activities to the pollution of agricultural soils along major roads and the pollution could pose negative health implications to human and animal health.